Application of UWB wireless MIMO connectivity inside ships - Al-Khateeb, Khalid A. Saeed; Hakak, Saqib; Alam, Zahirul (2014)
In this paper, Ultra wideband (UWB) technology is proposed for replacing the large amounts of wiring used in ships which can cause serious problems like electrical interference, short circuit fires and similar trouble.There are numerous applications of Wireless Sensor Networks (WSNs) like in target tracking, monitoring a large number of sensors at vital points with actuators, controllers etc.. However there are not many studies which focus on implementing this technology in Ships. Wireless communications can be difficult in ships due to many metallic structures. The proposed UWB technology is based on novel pulse shapes which are derived from mono cycle sine waves in the GHz range, which have been practically tested and found to comply with the FCC regulations, in terms of power levels and spectral mask limitations. The technique can be operated as a high bit rate fast digital personal area network (PLAN).The results obtained practically show that this wireless solution may provide cost-effective alternative to the huge amount of wiring and cables, which are used to interconnect sensors and peripheral devices to central digital control units.The proposed scheme has been analysed theoretically and implemented practically as well as by simulation. It gave sound results in terms of cost, speed, channel capacity as well as power and spectral mask compliance with FCC regulations.